The Effect of Financial Literacy and Income on the Effect of Investment Decisions - Nur Adillah (The Scientia Journal of Economics Issues, 2023)
The purpose of this research is to examine and measure the effect of income and financial literacy on investment decisions. The type of examination used is qualitative with the literature review method. Sources of data from books and journal articles serve as the type and source of data. This study found that investment decisions are not significantly influenced by financial literacy. Conclusion: (1) Multiple linear regression test shows that the positive constants and variable coefficients show a unidirectional relationship in the equation. (2) The T-test shows that the financial literacy variable has no significant effect on investment decisions; (3) It is known from the results of the F test that the income and financial literacy variables have a significant effect on the overall investment decision.